Neurotheology:: Brain-based Religious Experience - Jalaluddin Rakhmat (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2011)
Even though most men are occupied with gaining a livelihood and providing for their daily needs and show no concern for spiritual matters there lies within the nature of man an innate urge to seek the ultimate Real. In certain individuals, this force which is dormant and potential becomes awakened and manifest itself openly, thus leading to a series of spiritual perfections.